2010
DOI: 10.1007/s11746-010-1626-6
|View full text |Cite
|
Sign up to set email alerts
|

Flaking as a Pretreatment for Enzyme‐Assisted Aqueous Extraction Processing of Soybeans

Abstract: Soybean moisture content (7.2-12.8%) and conditioning temperature (51-79°C) during flaking were evaluated to determine their effects on oil and protein extraction and oil distribution among fractions produced in enzyme-assisted aqueous extraction processing (EAEP). Extractions were performed by using two-stage countercurrent EAEP at a 1:6 solids-to-liquid ratio with 0.5% protease (wt/g extruded flakes) at pH 9.0 and 50°C for 1 h. Oil extraction improved when using soybeans with moisture contents ranging from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 22 publications
(30 reference statements)
1
37
1
Order By: Relevance
“…Studies reported that cell walls together with the newly formed protein network from extrusion inhibit the release of oil [4,24,25]. Although extrusion can completely disrupt cell walls, different varieties of seeds require different extrusion conditions, such as, barrel temperature, feed moisture, and screw rotational speed [26,27]. In addition, the composition and confirmation of the formed protein network of each seed may not the same; therefore, using one variety of protease (Alcalase 2.4 L in the current study) to hydrolyze these protein networks may not result in the same degrees of protein hydrolyze.…”
Section: Model Fittingmentioning
confidence: 99%
“…Studies reported that cell walls together with the newly formed protein network from extrusion inhibit the release of oil [4,24,25]. Although extrusion can completely disrupt cell walls, different varieties of seeds require different extrusion conditions, such as, barrel temperature, feed moisture, and screw rotational speed [26,27]. In addition, the composition and confirmation of the formed protein network of each seed may not the same; therefore, using one variety of protease (Alcalase 2.4 L in the current study) to hydrolyze these protein networks may not result in the same degrees of protein hydrolyze.…”
Section: Model Fittingmentioning
confidence: 99%
“…Extensive research has been performed on enzyme-assisted aqueous extraction processing (EAEP) from soybeans [1][2][3][4][5][6][7][8][9][10] as an alternative to using hexane to extract edible oil from soybeans and a number of recent advances have been achieved [11]. In addition to eliminating the use of hazardous and polluting hexane, this water-and enzyme-based technology enables simultaneous fractionation of soybeans into oil-, protein-, and fiber-rich fractions suitable for converting into food, feed, and fuel.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the effects of enzyme use on oil, protein, and solids extraction yields from extruded full-fat soybean flakes. 17,30 Reducing enzyme exposure in EAEP decreased all extraction yields. Extraction yields were greater when using enzyme in both EAEP extraction stages (treatment 1) and moderately greater when using enzyme in the second stage only (treatment 2) compared to no enzyme use (treatment 3).…”
Section: Article ' Results and Discussionmentioning
confidence: 99%
“…16, 17 Oil extractability in countercurrent two-stage EAEP is 95À99% 15À17 and is as complete as commercial hexane extraction (95.0À97.5%); 3 however, overall free oil recovery is ∼83% compared to >95% for hexane extraction due to unrecovered oil in the skim fraction (∼14%). 15 Asian populations consuming large amounts of soybean products have lower risks of osteoporosis and some chronic diseases, most notably heart disease and cancer.…”
Section: à11mentioning
confidence: 99%
See 1 more Smart Citation